Cover Dance Sebagai Bentuk Ekspresi Penggemar K-Pop Di Kota Denpasar - Pramestiasri, Made Melly Anindita; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT The development of K-Pop music in Indonesia has its own appeal because of the visualization of K-Pop stars is increasingly popular. This made fans who initially only enjoyed K-Pop music slowly begin to follow the choreography of K-Pop stars when on stage. There are two points of view regarding the attractiveness of cover dance. First the attraction of cover dance is the totality of people who cover dance. Second, the euphoria of K-Pop fans when watching people who cover dance appear on stage. Through the cover dance the fans express their love by imitating the idol, suggesting that they are like the idol, then slowly they begin to be identified and sympathize with each other in their interactions with colleagues who cover dance or with K-Pop fans. Keywords: Cover Dance, K-Pop, Boygroup, Girlgroup.